EVALUATION OF FUNGICIDES AGAINST LEAF SPOT DISEASE OF APPLE ( OF APPLE (Malus domestica cv Malus domestica cv. red delicious . red delicious) CAUSED BY Alternaria Alternaria mali ROBERTSEVALUATION OF FUNGICIDES AGAINST LEAF SPOT DISEASE OF APPLE ( OF APPL - U. S. FAIS; V. KUMAR; P. VIJIMOLE (The Bioscan, 2024)
Present experiment was conducted to evaluate different fungicides for controlling Alternaria leaf spot of apple. Seven different treatments were evaluated in vitro and in vivo conditions., In vitro result revealed that Hexaconazole at concentrations 250,500,750 and 1000 ppm inhibited 100% growth of test pathogen concentration of followed by Difenconazole (72%, 88.9%, 95% and 100%) at 250, 500, 750 and 1000ppm respectively. Carbendazim (100%) at 750 and 1000 ppm. The least percent growth inhibition was found in case of Mancozeb (5.5%) at 250ppm. In vivo results revealed that Mancozeb + Carbendazim (0.025%) was found most effective and recorded significantly least disease incidence (20.05%) with per cent yield increased over check (6.03%) followed by Hexaconazole (5.25%), Difenoconazole (5%) and Copper oxy Chloride (4.06%). Hexaconazole is found second most effective for the control of Alternaria leafspot of apple.